Hubungan antara budaya: Kajian etnografi ke atas Kumpulan Wayang Kulit Sri Campuran Di Kelantan / Eyo Leng Yan - Eyo , Leng Yan (2021)
Malaysia is of diverse backgrounds that require each ethnic group to respect, tolerate and understand other cultures in order to ensure prosperity and harmony. However, issues related to ethnic conflict have never been resolved. Studies conducted by previous researchers formulating the barriers to intercultural relations are language, culture, religion, and perception that lead to prejudice, ethnocentrism and racial polarization that hinder inter-ethnic communication. This study uses intercultural communication disciplines to see the phenomenon of an intercultural relations in the performance of the Kelantan’s Wayang Kulit performed by the Sri Campuran Wayang Kulit Group. This group was chosen as the subject of the study as the characteristics of this group have ethnic coalition, that contribute to intercultural communication. This study examines three main aspects of Kelantan's Wayang Kulit performing arts, include the cultural aspects of Kelantan community (cultural context), the Sri Campuran Kelantan Group (micro cultural context) and intercultural communication in the Kelantan's Wayang Kulit performing arts, thus forming cultural relations (environmental context). Through ethnography approach and participating observation methods in five locations of the show and interviewing methods, there is a cultural connection between various ethnic groups in Kelantan and does not raise issues related to language, culture, religion and perception.